PENGARUH KINERJA KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN PERBANKAN DI BEI PADA TAHUN 2008-2011 - HANDAJANI, SUSANA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
The company's main objective is to increase corporate value through improved financial performance of the company, so the company will have a good condition or not bankruptcy. This study aims to examine the effect of financial distress on the financial performance of the banking company. This study uses secondary data from 30 banking companies listed in Indonesia Stock Exchange during the four years of the period 2008-2011 as the sample and have to meet certain criteria. The results indicate that financial distress affects financial performance. Only earnings per share are not significantly detrimental to financial distress.